Isolation and selection of maize plants rhizobacteria with the potential of entomopathogens against Spodoptera litura (Lepidoptera: Noctuidae) - Novri Nelly; Ujang Khairul; Ade Yulia Lestari; Hasmiandy Hamid; My Syahrawati (Society for Indonesian Biodiversity, 2020)
Abstract. Nelly N, Khairul U, Putri AY, Hamid H, Syahrawati MY. 2020. Isolation and selection of maize plants rhizobacteria with the potential of entomopathogens against Spodoptera litura F (Lepidoptera: Noctuidae). Biodiversitas 21: 753-758.  Spodoptera litura is a polyphagous pest that can be controlled with entomopathogen. Furthermore, Rhizobacteria derived from the rhizosphere of corn plants are expected to control this pest. This research, therefore, was conducted to obtain the entomopathogenic rhizobacteria to control S. litura derived from the rhizosphere of corn plants. Data sampling was carried out at corn plantations in West Pasaman Regency, while Isolation, selection, and testing of S. litura were conducted at the Biological Control Laboratory of the Plant Protection Department, Faculty of Agriculture, Andalas University. The method uses serial glowing techniques cultured on Nutrient Agar (NA) media, with the selected isolates tested for their ability as an entomopathogen against S. litura. The feed dip method given to S. litura larvae was used to test for rhizobacteria virulence determination with entomopathogen, used to observe the larvae mortality rate, percentage of pupae, and adult formed. Furthermore, observation of morphological and physiological characters was conducted on entomopathogenic rhizobacteria, with hypersensitive testing conducted on Mirabilis jalapa plants. The results of rhizobacterial isolation from corn rhizosphere obtained 12 entomopathogenic isolates. Deadly larvae of S. litura 51-91.11%, 0.00-8.89% pupae, and 0.00- 6.67% adult were formed. The gram test results obtained approximately 8;4 positive (+) and four negative isolates (-), respectively. Hypersensitivity test results found that one of 12 isolates caused necrotic reactions in Mirabilis jalapa. Therefore, a total of 11 rhizobacteria isolates are entomopathogenic and safe to be used as S. litura biological control agents.